Cyclic behavior of an innovative braced ductile thin shear panel. (August 2021) - Sun, Guohua; Bao, Cheng; Liu, Wenyuan; Fang, Youzhen
Abstract: This study aimed to investigate the cyclic behavior of an innovative braced ductile thin shear panel (BDSP) component consisting of a concentric rectangular thin shear panel, a surrounding flange plate, and X-shaped brace segments. A total of eight BDSP specimens at a one-third scale were designed, considering the influence of shear panel thickness, shear panel dimension, and stiffening rib space. The tests were performed by applying a reversed cyclic lateral load. All specimens exhibited a high initial lateral stiffness and stable cyclic behavior and failed in the shear panel region. The adoption of stiffening ribs reduced the ductility of test specimens but enhanced the lateral strength and energy dissipation. Pinching of the lateral force versus drift ratio was observed for the BDSP specimens without stiffening ribs, which exhibited considerably high deformability and limited energy dissipation. Additionally, the specimens without stiffening ribs experienced elastic shear buckling behavior and developed a tension field mechanism in the shear panel region along the main diagonal direction. The overstrength factor ( R Ω ) value of 1.4 was conservatively recommended for the BDSP specimens without stiffening ribs.